Assessment of adult awareness and perception of covid-19 vaccines on health status of urban dwellers in Nigeria (2016)
The outbreak of coronavirus 2019 (COVID-19) pandemic has significantly inflicted a danger on health, economy and social relations globally covering the six continents and around 2.7 million people had died after contracting the respiratory virus. The global pandemic has necessitated some drastic measures to curb its spread. It is uncertain whether these measures are known and their perception about the measures cannot be ascertained. This study assessed the awareness and perception of COVID-19 vaccine on the health status of urban adult dwellers in Nigeria. The four research questions that guided the study. The study employed correlational research type of non-experimental design. Purposive sampling technique was used to sample 300 participants that took part in the study. Only participants that had taken the COVID-19 vaccine were included in the study. One instrument, Adult Awareness and Perception of Covid-19 Vaccines on Health Status Questionnaire (APCVHSQ) with Cronbach Alpha reliability coefficient 0.85 was used for data collection. Data collected was analysed using descriptive statistic of frequency, percentages and mean as well as thematic analysis. The result revealed that majority of the adult population are aware of the various measures embarked upon to curb the spread of the virus (2.50<3.07). Moreover, adult population in Nigeria perception of covid-19 vaccine prevalence was relatively negative (2.50<2.60). In addition, majority 249 (81.6%) of the adult population believed that their health conditions were not worsened after taken Covid- 19 vaccine while 261 (84.2%) of the adult population in Nigeria did not find it difficult to cope with their daily activities after the vaccination. 48.4% had the higher cases of malaria associated with Covid-19 vaccination. It is suggested that more awareness campaign should be embarked upon by the agency responsible for mobilization to reduce the negative attitude of COVID-19 vaccine among the adult population.